Ultrafast dynamics of gallium vacancy charge states in β-Ga_{2}O_{3} - Arjan Singh; Okan Koksal; Nicholas Tanen; Jonathan McCandless; Debdeep Jena; Huili (Grace) Xing; Hartwin Peelaers; Farhan Rana (Physical Review Research, 2021)
Point defects in crystalline materials often occur in multiple charge states. Although many experimental methods to study and explore point defects are available, techniques to explore the nonequilibrium dynamics of the charge states of these defects at ultrafast (subnanosecond) timescales are rare. We present results from ultrafast optical-pump supercontinuum-probe spectroscopy measurements on β-Ga_{2}O_{3}. The probe absorption spectra shows defect absorption peaks at two energies, ∼2.20eV and ∼1.63eV, within the 1.3–2.5 eV probe energy bandwidth. The strength of the absorption associated with each peak is time dependent and the spectral weight shifts from the lower energy peak to the higher energy peak with pump-probe delay. Further, maximum defect absorption is seen for probes polarized along the crystal c axis. The time-dependent probe absorption spectra and the observed dynamics for all probe wavelengths at all pump-probe delays can be fit with a set of rate equations for a single multilevel defect. Based on first-principles calculations within hybrid density-functional theory, we attribute the observed absorption features to optical transitions from the valence band to different charge states of Gallium vacancies. Our results demonstrate that broadband ultrafast supercontinuum spectroscopy can be a useful tool to explore charge states of defects and defect dynamics in semiconductors.